2018
DOI: 10.21474/ijar01/7604
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Associated Urinary Tract Infection (Cauti) in Medical Ward, and Icu KFHH During Year 2017.

Abstract: Background: Catheter-associated urinary tract infection (CAUTI) is one of the most common hospital acquired infection. Objectives: determining the risk factors, causes and frequency of CAUTI among infected cases with CAUTI in King Fahad Hofuf hospital and to provide local evidence-based recommendations for prevention of CAUTI. Methods: It is a prospective surveillance study of CAUTI. The study was carried out at the Medical ward in King Fahad Hofuf hospital (KFHH) from May to August 2017. The study included al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…In the present study, the outcomes of CAUTI were increased duration of hospitalization and recovery of patients whereas a similar study conducted by Zahran et al [12] found that the outcomes of CAUTI were complete recovery among 98.5% of patients.…”
Section: Job Et Alcontrasting
confidence: 62%
See 1 more Smart Citation
“…In the present study, the outcomes of CAUTI were increased duration of hospitalization and recovery of patients whereas a similar study conducted by Zahran et al [12] found that the outcomes of CAUTI were complete recovery among 98.5% of patients.…”
Section: Job Et Alcontrasting
confidence: 62%
“…The decreased rate of CAUTI in ICU might be due to the increased aseptic environment than non ICU. A similar study conducted by Zahran et al [12]. on the comparison of the incidence rate of CAUTI among ICU and non ICU patients had found that the incidence rate is more in non ICU.…”
Section: Job Et Almentioning
confidence: 68%
“…In the present study, most patients presented only with a fever ( n = 23, 33%), and there was a positive association between the fever and CAUTI. Fever is a particularly common symptom among critically ill patients, and evaluation for CAUTI should be conducted if fever is present in catheterized patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the linezolid-resistant CoNS detected in the current study was isolated from a patient who was prescribed linezolid as an empirical therapy for upper respiratory tract infection. In the same context, Zahran et al 6 reported the linezolid prescribing practices to be extremely abusive in a hospital in Saudi Arabia where linezolid was the antibiotic to be most often prescribed for cases of catheter-associated urinary tract infections. Similarly, Kramer et al 7 analyzed the prescribing practices of linezolid in German hospitals and concluded that during the period from 2011 to 2016, linezolid prescribing has significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Linezolid overuse and extensive use are widely observed in clinical practices in both developed and developing countries due its excellent pharmacodynamic and pharmacokinetic properties 6,7 . This played a major role in the emergence of Grampositive linezolid-resistant strains 8 .…”
Section: Introductionmentioning
confidence: 99%